Orthodontic retainers: analysis of prescriptions sent to laboratories - Washington Komatsu Assumpção; George Kenji Bezerra Ota; Rívea Inês Ferreira; Flávio Augusto Cotrim-Ferreira (Dental Press Editora, 2012)
OBJECTIVE: To investigate the most commonly fabricated orthodontic retainers. METHODS: Information on the type and amount of maxillary and mandibular retainers produced in a three-month period was collected from six laboratories in the cities of São Paulo, Mauá and Guarulhos - Brazil. The retainers were grouped according to the total production. For the maxillary arch, the groups were: 1S - Begg retainer, 2S - Hawley retainer, 3S - transpalatal arch retainer, 4S - buccal resin-arch retainer and 5S - vacuum-formed retainer, Planas appliance, bonded lingual retainer and V-loop bonded lingual retainer. The groups relative to the mandibular arch were: 1I - 3-3 bonded lingual retainer (canine to canine), 2I - Hawley retainer and V-loop bonded lingual retainer, 3I - Begg retainer, 4I - buccal resin-arch retainer, vacuum-formed retainer and Planas appliance. The data were presented in box plots. Groups were compared using the Student's-t test with Bonferroni correction. RESULTS: The average of maxillary appliances fabricated ranged from 189.5 (1S) to 3.95 (5S). There were significant differences between groups 1S versus 5S and 2S versus 5S (p < 0.0001). Mean values for the mandibular retainers ranged from 55.3 (1I) to 4.2 (4I). Significant difference was observed between groups 2I and 4I (p < 0.0001). CONCLUSIONS: For the maxillary arch, the most requested retainers were Begg and Hawley retainers. Regarding the mandibular arch, bonded lingual retainers and Hawley retainer were the most frequent ones.